Faktor-Faktor Yang Mempengaruhi Kinerja Perusahaan - Michael Hidayat (Universitas Tarumanagara, 2019)
The Purpose Of This Research Is To Analyze Determinants Of Firm Performance In Non-Financial Companies Listed On Indonesia Stock Exchange. Determinants That Are Tested In This Research Include: Board Independence, Board Size, Firm Size, Firm Age, Liquidity, Leverage, Managerial Ownership, Female Board Members. The Object In This Research Is Non-Financial Companies Listed From 2011 Until 2014. The Population Of This Research Is 378 Non-Financial Companies. Sampling Techniques That Used In This Research Is Purposive Sampling. There Are 30 Non-Financial Companies Listed From 2011 To 2014 Which Met The Criterion Used As Sample. The Data Used Is Secondary Data That Collected From Financial Statement Of The Company. Analysis Method Of This Research Is Multiple Linier Regressions. The Result Of This Research Conclude That Board Independence, Leverage, And Female Board Members Have Influence Toward Firm Performance. Other Variable Such As Board Size, Managerial Ownership, Firm Size, Liquidity, And Age Firm Don’t Have Influence To Firm Performance.